Uji Validitas Konstruk Tes Wechsler Intelligence Scale For Children (WISC) - Medianta Tarigan; Fadillah . (Faculty of Ushuluddin and Humanities, 2021)
As one of the psychological instruments that successfully provides an overview of the level of intelligence of children, the Wechsler Intelligence Scale For Children (WISC) test needs to be evaluated its validity with psychometric test procedures. The Wechsler Intelligence Scale For Children (WISC) test consists of 10 subtests in which each subtest has many diverse items. This study included 315 kindergarten students with an age range of 5-6 years. The data obtained from it is then analyzed using confirmatory factor analysis to test the validity of the construct. This study showed that the model had a good fit with a p-value of 0.066 and an entire subtest fit.